EFEKTIVITAS PENERAPAN POS PEMBERDAYAAN MASYARAKAT DI DESA BACANG DALAM TINGKAT KESEJAHTERAAN KELUARGA - Ajeng Dinantika Rahayu; Balqis Triaya Dewanti; Mikha Tiffani; Shifa Aulia Maghfiroh; Triayu Nur Afifah (Universitas Pahlawan Tuanku Tambusai, 2022)
The level of family welfare in Indonesia is still considered stagnant and has not shown a significant increase. The number of programs from the government which are allegedly able to help strengthen family welfare, is not enough to produce a prosperous family. Several studies have stated that the level of family welfare is influenced by several factors, one of which is the existence of a community empowerment forum in which there are activities to support the family economy. Assessing this, the Head of the Damandiri Foundation, Dr. Haryono Suyono, M.A., Ph.D, established the Pos Community Empowerment (Posdaya) to help improve the level of family welfare through quality empowerment. The Community Empowerment Post (Posdaya) is a forum for communication, advocacy, information, education, and an integrated forum for strengthening family welfare activities. Through empowerment activities in the Community Empowerment Post (Posdaya) it is hoped that it can improve family welfare through the establishment of family functions as a whole. This study uses a qualitative method. Considering the purpose of the research is to dig deeper into the data in the field, so that the qualitative method is the right choice. The research theory is based on the theory of effectiveness. The theory is in line with the desired research results, namely if a result or output of an activity is getting closer to the target, it means that the effectiveness is higher. Data analysis techniques in this study are data reduction, data display, and conclusion drawing/verification. The results showed that Posdaya Bacang was considered capable of increasing the level of family welfare.